Efetividade de modelos de gestão por competências: um estudo comparativo de casos - Staron, Silvia Cristina Antonio (2016)
The current competitive environment drives the area of human resources for strategic guidance in the review of its people management practices. Company's strategic positioning, in line with the strategic planning of human resources, allows to the organization to reap the fruits in organizational performance. This research aimed to study the design of competency-based management models, theoretical assumptions, processes involved in the context (internal and external environment), content (strategic guidelines, individual competence, levels of complexity), processes (model construction and model support), model effectiveness (use and outcomes) and institutionalization of the model. In the format of a comparative study of cases, this research analyzes three companies of similar activities that have implemented a competency management model in the same period. The methodology consists of comparative case study of descriptive and exploratory nature with a qualitative approach. Data were collected through semistructured interviews, documentary analysis, bibliography and non-participant observation. As main results, from the three surveyed companies, it was found that in two of them the model was deployed and it has been supported with qualitative and quantitative outcomes during the period, highlighting the process since its construction, with the involvement of key company executives. In one of the companies, the process was built, but did not support the model over time.